2013
DOI: 10.1371/journal.pone.0072318
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Small Peptide Fragment as an Inhibitor of Insulin Fibrillation Process: A Study by High and Low Resolution Spectroscopy

Abstract: A non-toxic, nine residue peptide, NIVNVSLVK is shown to interfere with insulin fibrillation by various biophysical methods. Insulin undergoes conformational changes under certain stress conditions leading to amyloid fibrils. Fibrillation of insulin poses a problem in its long-term storage, reducing its efficacy in treating type II diabetes. The dissociation of insulin oligomer to monomer is the key step for the onset of fibrillation. The time course of insulin fibrillation at 62°C using Thioflavin T fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 62 publications
3
71
0
Order By: Relevance
“…MD simulation gives the detailed information of complex formation at the atomic level5152. In explicit solvent medium Chelerythrine adjust its position with respect to initial docked state53.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulation gives the detailed information of complex formation at the atomic level5152. In explicit solvent medium Chelerythrine adjust its position with respect to initial docked state53.…”
Section: Resultsmentioning
confidence: 99%
“…In order to generate the random-coil structure for L25P, a simulation of 5 ns was performed in water box with fully extended linear structure. All the peptide structures were processed for gas-phase energy minimization and simulated annealing as per the protocol reported in the literature [28]. POPC bilayer was prepared with the peptides embedded within the bilayer and solvated with a 10Å water box (SPC water models [29]).…”
Section: Methodsmentioning
confidence: 99%
“…All the simulations were carried out in Desmond using OPLS_2005 force-field [30] at constant temperature and pressure of 300K and 1atm respectively. All the initial setting of system minimization, equilibrium and temperature control and various remaining simulation parameters were similar to the published protocol [28]. The described systems were continued for a simulation spanning 50 ns time scale.…”
Section: Methodsmentioning
confidence: 99%
“…Computational studies reported in this paper were performed with a random coil structure predicted for KK13 based on simulated annealing (SA) as the starting structure. 35 The incremental temperature interval of SA includes a constant temperature equilibration step of 10 ps intended to provide uniform temperature distribution across the system. 33 The linear sequence of KK13 was processed with gas phased energy minimization using the ff99SB-ILDIN force field which clears all the stearic clashes.…”
Section: Computational Modelingmentioning
confidence: 99%